Active sites of peptide from Arg‐Ser‐Ser protect against oxidative stress in HepG2 cells. Issue 4 (11th December 2021) - Liang, Jiaxi; Zhang, Ruier; Zhao, Jiaxin; Liu, Huifan
Abstract : Peptide Arg‐Ser‐Ser (RSS) was derived from Lactobacillus amylolyticus co‐incubated with edible Dendrobium aphyllum. Here, we further examined the antioxidative effects of RSS in HepG2 cells subjected to 2, 2‐azobis(2‐methylpropanimidamidine) dihydrochloride‐induced oxidative stress. RSS protected cells by eliminating the level of reactive oxygen species (ROS). The protein expression of antioxidant enzymes, Nrf2 and Keap1 determined by western blot, indicated that RSS might maintain cellular homeostasis by directly scavenging free radicals instead of by enzymatic system. Furthermore, quantum chemistry calculations and a characterization of electronic‐related properties showed that the highest occupied molecular orbital energy distribution was on arginine residue. Pre‐treatment with RSS with the active site methylated resulted in increased ROS levels, thereby verifying that N2 ‐H3 is the active site for antioxidant activity. Our findings provide valuable insights into the antioxidant activity of RSS and a basis for developing antioxidant functional foods.